Macroeconomic Sensitivity and Financial Performance on Islamic Banks Profitability - anafil windriya; Mashudi Mashudi; Luluk Fauziah; Shinta Marta Lorenza; Irena Rahmawati (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to determine and analyze the effect of NOM sensitivity on inflation, CAR, NPF, FDR, OER, and company size (Size) on profitability in Islamic commercial banks in Indonesia from 2017 to 2022. The population in this study are all Islamic Banks in Indonesia. The sample used is purposive sampling. There are 7 Islamic Banks that are the sample in this research object. The method used is linear regression, where this method is used for hypothesis testing. In this study, the measurement of the coefficient of determination, the F significance test, and the t significance test were used. This measurement is done to determine how much influence between variables. The test results show that simultaneously NOM sensitivity on inflation, CAR, NPF, FDR, OER, effect on profitability. However, the t significance test shows only OER has a significant negative effect on the profitability of Islamic commercial banks in Indonesia. Meanwhile, NOM's sensitivity to inflation, CAR, NPF, and firm size (Size) have no significant effect on the profitability of Islamic Banks in Indonesia. The hypothesis regarding the Financing to Deposit Ratio (FDR) has a positive effect on the profitability of Islamic banks has not been proven.